ANALISIS INVESTASI PENGEMBANGAN POTENSI PARIWISATA PADA PEMBANGUNAN WADUK JEHEM DI KABUPATEN BANGLI - Nadiasa, Mayun; Widnyana Maya, D. N. K.; Norken, I N. (Jurnal Ilmiah Teknik Sipil; Vol. 14, No. 2 Juli 2010)
The Jehem reservoir tourism object which will be built side by side with the Jehem reservoir, is located in the watershed of Melangit river and still in Bangli Hill Ecotourism area. This potential tourism object is of the indirect benefits (secondary benefit) from the reservoir development. Objective of the study is to analyze the financial feasibility on the tourism sector development in this area using methods of Net Present Value (NPV), Internal Rate of Return (IRR), Benefit Cost Ratio (BCR), Payback Period (PP) and Sensitivity Analysis. Base on financial analysis it is obtained that the Net Present Value (NPV) is of Rp19,397,935,290.73, Internal Rate of Return (IRR) 23.22%, Benefit Cost Ratio 1.802, and Payback Period will be achieved at the 9th year from the period of investment planning for 20 years. With NPV value is greater than zero, IRR value is greater than the investment rate, and BCR value is greater than or equal to one, and Payback Period is reached before the period of the investment plan achieved, then the investment plan is categorized as feasible. The results of sensitivity analysis also show the feasible values for this investment plan.
Keywords: Investment Analysis, Ecotourism, Jehem Reservoir, Financial Aspects